Identifikasi Perilaku Gen Z Atas Penggunaan Fintech - Edward, Robert; Tambun, Sihar; Ainy, Farah Nurul (Future Science, 2025)
Use of fintech. This research method uses a qualitative approach with literature studies. Sources obtained from journal articles, online news, youtube and several interviews were conducted. The process of coding and visualizing research results uses NVivo Software. This research explains that the behavior of generation z on the use of fintech is that generation z prefers fintech applications that provide easy access, fintech also makes transactions faster and generation z is also now more interested in making investments because they realize that there will be a high cost of living and they also realize that lifestyle in this era is expensive. Therefore, for now Generation Z prefers to invest so that their finances continue to grow. This research provides an overview of how Generation Z will always be connected in the world of fintech, especially when it comes to transacting and investing and how socioeconomic factors affect their financial decisions.